Willing executors of Hitler's will? the Goldhagen controversy, political analysis and the holocaust - Hay, Colin (2000)
Comenta el libro de Daniel Jonah Goldhagen, "Hitler's Willing Executioners: Ordinary Germans and the Holocaust", asi como los comentarios y discusiones que ha suscitado
Keywords: Antisemitismo; Alemania